ANALISA KONSEP UNIVERSALITAS NILAI ISLAM DAN PANCASILA (STUDI PEMIKIRAN YUDI LATIF) - Rizaldy Purnomo Pedju (Potret Pemikiran, 2019)
This article discusses the analysis of the universality concept of Islamic Values and Pancasila in yudi latif's discussion contained in his works. The successor to the Pancasila pride, was able to actualize Pancasila with historical and rational support, by not forgetting the religious, social, cultural and political values in the ideology of Pancasila. The concept of yudi latif in the presentation of his thoughts is able to bring precepts in Pancasila using Indonesian specialties, by providing historical space in the narrative that supports and does not eliminate religiosity, diversity, consultative democracy and social justice. The concept of universality in the values of Islam and Pancasila is expected to be able to dismiss the narratives of radicalism, islamophobia which is developed rapidly developed. This latif thought, is able to provide ontological, epistemological, and axiological understanding between Islam and Pancasila as we.ll as the two things that interrelated to one another.                                                             Keywords : Yudi Latif;  Analysis; Universality; Islamic Value; Pancasila Value Artikel ini membahas tentang analisa konsep universalitas Nilai Islam dan Pancasila dalam pemikiran Yudi Latif yang termaktub dalam karya-karyanya. Bapak penerus marwah Pancasila ini, mampu megaktualisasikan Pancasila dengan pendekatan historis dan rasional, dengan tidak melupakan nilai agama, sosial, budaya dan politik dalam pengalian ideologi Pancasila. Konsep yudi latif dalam penyajian pemikirannya mampu membawa sila per sila dalam Pancasila kedalam khasanah khas keindonesiaan, dengan memberikan ruang sejarah dalam narasi pemikirannya serta tidak melupakan unsur religiusitas, sebagaimana dalam pembahasan penulis bahwa nilai islam dan nilai Pancasila terkandung dalam Ketauhidan, Kemanusiaan Universal, Persatuan dalam Keragaman, Demokrasi Permusyawaratan serta Keadilan Sosial. Konsep universalitas nilai islam dan Pancasila diharapkan mampu menepis narasi-narasi radikalisme, islamophobia yang marak berkembang belakangan ini. Pemikiran yudi latif secara aktual, mampu memberikan integrasi pemahaman antara islam dan Pancasila secara ontologis, epistemologis, dan aksiologis merupakan dua hal yang saling terhubung satu sama lainnya. Kata Kunci : Yudi Latif; Analisa; Universalitas; Nilai Islam; Nilai Pancasila